Nanocrystalline Aluminum Oxide Coating Fiber Optic Vapour Sensors - Renganathan1, B.; Sastikumar2, D.; Srinivasan3, R.; Ch, A.; Bose2, ra; Ganesan1, A.R. (Asian Journal of Chemistry, 2013)
Fiber optic sensor based on cladding modification has been developed for detecting various gas emissions such as ammonia, methanol and ethanol. The change in the refractive index of the cladding and the phenomena of evanescent wave absorption forms the underlying principle. The as-prepared aluminum oxide annealed at 1200 ºC was used as a gas sensing material. The spectral characteristics of the gas sensor was studied for different concentrations (0-500 ppm) of gases. The sensor exhibits a linear variation in the output light intensity with the concentration. The light intensity as a function of gas concentration exhibits a linear increase for ammonia, ethanol and methanol as-prepared Al2O3. However, 1200 ºC annealed Al2O3 shows decreased sensitivity for methanol gas. The enhanced gas sensitivity and selectivity of the sensor is discussed. The time response characteristics of the sensor are also reported.